Transport Against HIV/AIDS : Synthesis of Experience and Best Practice Guidelines - World Bank (Washington, DC, 2014)
The transport sector is especially vulnerable to HIV/AIDS. Transport workers including long distance truck drivers, seafarers, airline crews and infrastructure construction workers spend long periods of time away from home, often endure harsh working conditions, and may engage in unsafe behavior that can lead to infection. Their mobility makes it difficult to access health information and treatment, or to maintain drug regimen. Transport hubs and construction sites are often considered hot spots due to the influx and interaction that take place among the mobile workers. Furthermore, the sector works as a vector for HIV spread as the opening of new roads connects low and high prevalence areas. The World Bank transport group has been proactively mainstreaming HIV response by assisting client governments to design and implement sector-level interventions. Programs are most developed in the highest prevalence areas, initially in Sub-Sahara Africa and now also in Asia. Support to the sector includes organizing training events to increase staff awareness and knowledge, providing access to research materials, and securing funds to develop or scale up intervention programs. To institutionalize the response, explicit provisions for HIV prevention have been embedded in the standard bidding document. The group also collaborates with local workers organizations with the help of International Transport Workers Federation and the International Labor Organization. Some lessons learned are: (i) strategies must be crafted to meet the specific needs of the country in accordance with the local culture and unique epidemic situations; (ii) coordination with the health sector and the national AIDS authority is necessary for effective program design; and (iii) involving stakeholders from local communities is key to program success.